A pore-level direct numerical investigation of water evaporation characteristics under air and hydrogen in the gas diffusion layers of polymer electrolyte fuel cells. (February 2019) - Safi, Mohammad Amin; Mantzaras, John; Prasianakis, Nikolaos I.; Lamibrac, Adrien; Büchi, Felix N.
Highlights: 3D pore‐level direct simulations of water evaporation in anode/cathode GDLs of PEFCs. Relative humidity boundary layer in a porous GDL has been accurately resolved in 3D. Evaporation in H2 up to four times larger than that in air at temperatures 30–80°C. Evaporation induced flows in H2 are large and act against diffusion towards catalyst. Growth of water vapor boundary layer with rising temperature suppresses evaporation. Abstract: During the operation of polymer electrolyte fuel cells (PEFC) liquid water clusters generated due to electrochemical reactions in the gas diffusion layers (GDL) create a resistance against gas transport towards the catalyst layers (CL), and hence must be efficiently removed to maintain the cell performance, a process often realized by means of forced evaporation. Water accumulation is of interest not only for the cathode GDL but also for the anode GDL, particularly under thermoneutral cell operation whereby liquid water can be added to either anode or cathode channel flows. Although many works studied water evaporation in air and especially at moderate temperatures, less effort has been devoted in investigating evaporation at elevated temperatures and at the anode side, where hydrogen flows in the gas channels. In this work, direct numerical simulation is used to characterize evaporation at pore level for both anode and cathode sides and at different temperatures (up to 80 °C), for which experimental data are rare and micro-scale transport is often difficult to assess in the laboratory. Realistic water distribution and porous GDL geometry, acquired from X-ray tomography, have been used while regularized distributions of liquid water are further considered in order to investigate evaporation at various saturation levels. Key results indicate that (a) the water evaporation rate in hydrogen flows can be up to 4 times larger than the corresponding one in air flows at the same gas stream velocity and temperature, (b) the predicted vertical evaporation-induced velocities under hydrogen are an order of magnitude bigger than the corresponding ones under air and they can grow large enough at elevated temperatures to potentially hamper hydrogen transport towards the CLs.